Discovery of imidazo[1, 5-a]pyridines and -pyrimidines as potent and selective RORc inverse agonists. Issue 15 (1st August 2015) - Fauber, Benjamin P.; Gobbi, Alberto; Robarge, Kirk; Zhou, Aihe; Barnard, Adrian; Cao, Jianhua; Deng, Yuzhong; Eidenschenk, Céline; Everett, Christine; Ganguli, Arunima; Hawkins, Julie; Johnson, Adam R.; et al.
Graphical abstract